Sealant for manufacturing new energy automobile and production method thereof

By adding composite tackifier and high-temperature modification components in the preparation process of new energy vehicle sealant, the problem of insufficient bond strength and high-temperature resistance of sealant is solved, and higher bond strength and high-temperature resistance are achieved, ensuring the stability and safety of sealant under various environmental conditions.

CN119505754AInactive Publication Date: 2025-02-25ANHUI GUXINXIN MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411467147.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119505754A_ABST
    Figure CN119505754A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sealants, and discloses a sealant for manufacturing a new energy automobile and a production method thereof, the sealant comprises the following raw materials: acrylic acid, butyl methacrylate, acrylamide, glycidyl acrylate, a composite tackifier, deionized water, benzoyl peroxide, a high-temperature-resistant modified component, a filler, a dispersant and a coalescing agent; wherein the structure of the composite tackifier contains an unsaturated alkenyl functional group and a catechol structure, so that the bonding strength of the sealant is effectively improved; the structure of the high-temperature-resistant modified component contains a large amount of silicon and rigid benzene ring structures, so that the prepared sealant has excellent high-temperature resistance, the service life of the sealant is prolonged, the sealing property of the sealant is maintained, and the stability and safety of the sealant under various environmental conditions are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sealants, and in particular to a sealant for manufacturing new energy vehicles and a production method thereof. Background Art

[0002] Sealant is a sealing material with adhesive properties that can deform with the shape of the sealing surface and is not easy to flow. It is mainly used to fill the gaps in the structure to act as a sealant. It is widely used in construction, automobiles, electronics, aerospace, medical and other fields. Among them, in the manufacturing process of new energy vehicles, the introduction of sealants is crucial to ensure the safety of various vehicle components, extend service life and improve overall performance.

[0003] As an important material in the manufacture of new energy vehicles, sealants are used for sealing, connecting and fixing battery packs, car bodies, power batteries, engines and other parts. In particular, polyacrylate sealants, as a new type of environmentally friendly material, have gradually attracted attention and favor in the new energy vehicle sealant market with their excellent performance characteristics, such as high strength, high elasticity, excellent weather resistance and excellent chemical corrosion resistance. With the development of science and technology, there are also various requirements for the performance of sealants used in the manufacture of new energy vehicles. Compared with ordinary sealants, sealants for new energy vehicles need to have higher bonding strength to avoid interface damage or delamination between the adhesive layer and the bonded material during use due to the poor bonding strength of the sealant, and then cracking, water leakage and other problems, thereby affecting the stability and safety of the entire system. In addition, sealants for new energy vehicles need to have excellent high temperature resistance to ensure that during the operation of the vehicle, even in the face of the heat generated by the battery and motor and the high temperature challenge of the external environment, they can still maintain a stable sealing and bonding effect. Therefore, sealants for new energy vehicles need to have excellent bonding strength and high temperature resistance to ensure their stability and safety under various environmental conditions.

[0004] In the prior art, optimization of basic materials is one of the main means to improve the performance of sealants. For example, the invention patent with publication number CN114032036B discloses a high-temperature resistant UV-curing sealant and a preparation method thereof. The invention is prepared by mixing acrylic monomers with photoinitiators, heating and dissolving them completely, and then mixing and grinding with modified acrylic esters, hydrocarbon resins, reinforcing fillers and additives, so that the prepared sealant has good high-temperature resistance. Therefore, the sealant can be modified by preparing additives with high bonding strength and high-temperature resistance to obtain a sealant with excellent bonding strength and high-temperature resistance. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a sealant for manufacturing new energy vehicles and a production method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A sealant for manufacturing new energy vehicles comprises the following raw materials in parts by weight: 50 to 60 parts of acrylic acid, 20 to 30 parts of butyl methacrylate, 10 to 20 parts of acrylamide, 5 to 10 parts of glycidyl acrylate, 4 to 8 parts of composite tackifiers, 20 to 40 parts of deionized water, 0.5 to 1.5 parts of benzoyl peroxide, 3 to 6 parts of high temperature resistant modified components, 6 to 8 parts of fillers, 1 to 3 parts of dispersants, and 1 to 2 parts of film-forming aids.

[0008] Furthermore, the preparation method of the composite tackifier comprises the following steps:

[0009] D1: Under nitrogen protection, 1,3-diamino-2-propanol, 2,3-dichloropropylene and dimethyl sulfoxide solution were stirred and mixed, and stirred at a constant temperature of 70-80°C for 5-10 hours, and then discharged after cooling to room temperature to obtain an intermediate material;

[0010] D2: Under continuous nitrogen conditions, the intermediate material and 3,4-dihydroxybenzoic acid were added to N-methylpyrrolidone, stirred evenly, and then an esterification catalyst was added. The system temperature was raised to 95-105°C, stirred for 4-8 hours, and the solvent was removed by rotary evaporation to obtain a composite tackifier.

[0011] Furthermore, in step D2, the esterification catalyst is any one of p-toluenesulfonic acid, aminosulfonic acid or trifluoromethanesulfonic acid.

[0012] Furthermore, the preparation method of the high temperature resistant modified component comprises the following steps:

[0013] DD1: under the action of the accelerator, polyphenylene ether and 4-bromobutyric acid are added to the xylene solution, magnetically stirred evenly, the temperature is raised to 75-85°C, stirred for 5-7 hours, and discharged to obtain modified polyphenylene ether;

[0014] DD2: Add modified polyphenylene ether, trimethylsilyl alcohol and N,N-dimethylformamide into the reaction kettle, stir evenly, add p-toluenesulfonic acid, stir at a constant temperature of 95-105°C for 5-7h, cool and discharge the material to obtain a high temperature resistant modified component.

[0015] Furthermore, in step DD1, the number average molecular weight of the polyphenylene ether is 500 to 3000.

[0016] Furthermore, in step DD1, the promoter is any one of sodium carbonate, potassium carbonate or sodium bicarbonate.

[0017] Furthermore, in step DD2, the mass ratio of the modified polyphenylene ether to trimethylsilyl alcohol is 1:0.1-0.3.

[0018] Furthermore, the filler is any one of calcium carbonate, hydrotalcite or titanium dioxide; the dispersant is any one of sodium tripolyphosphate, sodium hexametaphosphate or sodium pyrophosphate; and the film-forming aid is any one of 1,2-propylene glycol, propylene glycol methyl ether acetate or methyl benzyl alcohol.

[0019] A method for producing a sealant for a new energy vehicle comprises the following steps:

[0020] (i) adding acrylic acid, butyl methacrylate, acrylamide, glycidyl acrylate, composite tackifier and deionized water into a reaction kettle, stirring evenly with magnetic force, passing nitrogen, exhausting air, adding benzoyl peroxide into the reaction kettle, raising the system temperature to 60-70° C., stirring for 1-3 hours, and obtaining a mixture;

[0021] (ii) Add high temperature resistant modified components, fillers, dispersants and film-forming aids to the mixture, stir evenly at room temperature to obtain a sealant.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention effectively improves the bonding strength and high temperature resistance of the sealant by adding a composite tackifier and a high temperature resistant modified component during the preparation of the sealant, prolongs the service life of the sealant, and ensures its stability and safety under various environmental conditions.

[0024] (2) The present invention prepares a composite thickener containing unsaturated olefinic functional groups in its structure, and cross-links and polymerizes the composite thickener with acrylic acid, butyl methacrylate, acrylamide, and glycidyl acrylate monomers to form a mixture with a high degree of cross-linking, thereby making the interface bonding tighter, reducing the gaps and defects between the interfaces, and improving the cohesive force between molecules. On the one hand, it can enhance the bonding strength of the sealant and improve the adhesion of the sealant to the substrate. On the other hand, the higher cross-linking density limits the movement of the polyacrylate molecular chain, which can improve the sealant's resistance to high temperatures and maintain its stability in high temperature environments. In addition, the catechol structure in the composite thickener can further improve the bonding strength of the sealant, effectively avoiding interface damage or delamination between the adhesive layer and the adhered material, which would lead to cracking, water leakage, and other problems in the sealant.

[0025] (3) The present invention prepares a high temperature resistant modified component as a filler modifier for the sealant. Since the high temperature resistant modified component contains a large amount of silicon and rigid benzene ring structure, the decomposition temperature of the colloid is increased, and the damage to the molecular chain during the high temperature process is reduced. It can produce a synergistic effect with the composite thickener, so that the prepared sealant has excellent high temperature resistance. Even in a high temperature environment, it can maintain structural stability and chemical inertness, thereby extending the service life of the sealant and maintaining the sealing of the sealant, thereby ensuring its safety and reliability in use.

[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 This is an infrared spectrum test chart of the intermediate material and the composite tackifier prepared by the present invention.

[0029] Figure 2 The infrared spectrum test charts of the polyphenylene ether, modified polyphenylene ether and high temperature resistant modified components prepared in the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The preparation methods of the composite tackifier and the high temperature resistant modified component in the following examples and comparative examples of the present invention are as follows:

[0032] 1. Preparation of composite tackifier

[0033] D1: Add 0.9 g of 1,3-diamino-2-propanol and dimethyl sulfoxide solution to a nitrogen-protected reactor, stir evenly, then add 1.5 g of 2,3-dichloropropylene to the reactor, mix evenly, turn on the heating until the temperature in the reactor reaches 75°C, stir at constant temperature for 8 hours, stop heating and remove nitrogen, cool to room temperature and then discharge to obtain an intermediate material;

[0034] D2: Under continuous nitrogen conditions, 5 g of the intermediate material was added to N-methylpyrrolidone, ultrasonically treated for 20 min, and then 1.4 g of 3,4-dihydroxybenzoic acid was added and stirred evenly. Then 0.1 g of p-toluenesulfonic acid was added. After the addition was completed, the system temperature was raised to 100 ° C and stirred for 6 h. After rotary evaporation to remove the solvent, a composite thickener was obtained.

[0035] The intermediate material and composite tackifier were analyzed by infrared spectrum using TENSOR-27 Fourier infrared spectrometer. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of the intermediate material, 3041cm -1 The characteristic absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 3285cm -1 The characteristic absorption peak of OH in the hydroxyl group appears at 3390 cm -1 The characteristic absorption peak of NH appears at 1408cm -1 The characteristic absorption peak of CN appears at 3019cm -1 The characteristic absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 3410 cm -1 The characteristic absorption peak of NH appears at 1415 cm -1 The characteristic absorption peak of CN appears at 1740cm -1 The characteristic absorption peak of the ester group C=O appears at .

[0036] Technical principle: In the composite thickener, firstly, the amino group in the structure of 1,3-diamino-2-propanol can undergo continuous and stable substitution reaction with the halogen functional group in the structure of 2,3-dichloropropylene. This process leads to the continuous extension of the molecular chain, and finally forms a polymer containing unsaturated olefinic and hydroxyl groups in the structure, namely the intermediate material; secondly, the hydroxyl group in the structure of the intermediate material is used as the active site, and under the catalysis of p-toluenesulfonic acid, it reacts with the carboxyl group in the structure of 3,4-dihydroxybenzoic acid, thereby introducing 3,4-dihydroxybenzoic acid into the structure of the intermediate material through chemical bond connection to obtain the composite thickener.

[0037] 2. Preparation of high temperature resistant modified components

[0038] DD1: Add 5 g of polyphenylene ether with a number average molecular weight of 2500 and xylene solution into a reactor, stir evenly with a magnetic stirrer, add 1.2 g of 4-bromobutyric acid and 0.05 g of sodium carbonate into the reactor under nitrogen protection, stir evenly, raise the temperature to 80°C, keep stirring at this temperature for 6 hours, and discharge the material to obtain modified polyphenylene ether;

[0039] DD2: Mix 5g of modified polyphenylene ether with N,N-dimethylformamide, pour into a reactor, start stirring until a uniform solution is formed, pass nitrogen, exhaust the air, add 1g of trimethylsilyl alcohol and 0.02g of p-toluenesulfonic acid, stir at a constant temperature of 100°C for 6h, wait for the material to cool naturally, discharge the material, and obtain a high temperature resistant modified component.

[0040] The infrared spectrum of polyphenylene ether, modified polyphenylene ether and high temperature resistant modified components was analyzed by TENSOR-27 Fourier transform infrared spectrometer. Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of polyphenylene ether, 3406cm -1 The characteristic absorption peak of OH in the hydroxyl group appears at 3032cm -1 The characteristic absorption peak of CH in the benzene ring appears at 1045cm -1 The characteristic absorption peak of ether bond COC appears at 3046cm -1 The characteristic absorption peak of CH in the benzene ring appears at 1030cm -1 The characteristic absorption peak of ether bond COC appears at 1741cm -1 The characteristic absorption peak of the carboxyl group C=O appears at 3025cm -1 The characteristic absorption peak of CH in the benzene ring appears at 1060cm -1 The characteristic absorption peak of ether bond COC appears at 1755cm -1 The characteristic absorption peak of the ester group C=O appears at 1264 cm -1 The characteristic absorption peak of C-Si appears at the position, and the absorption peak of the carboxyl group disappears.

[0041] Technical principle: In the high temperature resistant modified component, firstly, under the action of sodium carbonate, the hydroxyl group in the polyphenylene ether structure and the halogen functional group in the 4-bromobutyric acid structure undergo a substitution reaction to obtain a modified polyphenylene ether containing a carboxyl group in the structure; secondly, under the action of p-toluenesulfonic acid, the carboxyl group in the modified polyphenylene ether structure can further undergo an esterification reaction with the hydroxyl group in the trimethylsilyl carbinol structure, thereby grafting the trimethylsilyl carbinol into the structure of the polyphenylene ether to obtain a high temperature resistant modified component.

[0042] Example 1

[0043] Preparation of sealant

[0044] (i) 50 g of acrylic acid, 20 g of butyl methacrylate, 10 g of acrylamide, 5 g of glycidyl acrylate, 4 g of a composite tackifier and 20 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 0.5 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was raised to 60° C. and stirred for 1 hour to obtain a mixture;

[0045] (ii) Add 3 g of high temperature resistant modified component, 6 g of calcium carbonate, 1 g of sodium hexametaphosphate and 1 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0046] Example 2

[0047] Preparation of sealant

[0048] (i) 55 g of acrylic acid, 25 g of butyl methacrylate, 15 g of acrylamide, 8 g of glycidyl acrylate, 6 g of a composite tackifier and 30 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 1 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was raised to 65° C. and stirred for 2 h to obtain a mixture;

[0049] (ii) Add 5 g of high temperature resistant modified component, 7 g of calcium carbonate, 2 g of sodium hexametaphosphate and 1.5 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0050] Example 3

[0051] Preparation of sealant

[0052] (i) 60 g of acrylic acid, 30 g of butyl methacrylate, 20 g of acrylamide, 10 g of glycidyl acrylate, 8 g of a composite tackifier and 40 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 1.5 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was raised to 70° C. and stirred for 3 hours to obtain a mixture;

[0053] (ii) Add 6 g of high temperature resistant modified component, 8 g of calcium carbonate, 3 g of sodium hexametaphosphate and 2 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0054] Comparative Example 1

[0055] Preparation of sealant

[0056] (i) 55 g of acrylic acid, 25 g of butyl methacrylate, 15 g of acrylamide, 8 g of glycidyl acrylate, 6 g of a composite tackifier and 30 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 1 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was raised to 65° C. and stirred for 2 h to obtain a mixture;

[0057] (ii) Add 7 g of calcium carbonate, 2 g of sodium hexametaphosphate and 1.5 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0058] Comparative Example 2

[0059] Preparation of sealant

[0060] (i) 55 g of acrylic acid, 25 g of butyl methacrylate, 15 g of acrylamide, 8 g of glycidyl acrylate and 30 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 1 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was increased to 65° C. and stirred for 2 h to obtain a mixture;

[0061] (ii) Add 5 g of high temperature resistant modified component, 7 g of calcium carbonate, 2 g of sodium hexametaphosphate and 1.5 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0062] Comparative Example 3

[0063] Preparation of sealant

[0064] (i) 55 g of acrylic acid, 25 g of butyl methacrylate, 15 g of acrylamide, 8 g of glycidyl acrylate, 6 g of 3,4-dihydroxybenzoic acid and 30 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 1 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was increased to 65° C. and stirred for 2 hours to obtain a mixture;

[0065] (ii) Add 5 g of high temperature resistant modified component, 7 g of calcium carbonate, 2 g of sodium hexametaphosphate and 1.5 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0066] Comparative Example 4

[0067] Preparation of sealant

[0068] (i) 55 g of acrylic acid, 25 g of butyl methacrylate, 15 g of acrylamide, 8 g of glycidyl acrylate and 30 g of deionized water were added to a reaction kettle, magnetically stirred, nitrogen was passed through, and after the air was exhausted, 1 g of benzoyl peroxide was added to the reaction kettle. After the addition was completed, the system temperature was increased to 65° C. and stirred for 2 h to obtain a mixture;

[0069] (ii) Add 7 g of calcium carbonate, 2 g of sodium hexametaphosphate and 1.5 g of propylene glycol methyl ether acetate to the mixture, stir evenly at room temperature to obtain a sealant.

[0070] Performance testing:

[0071] The sealants prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were uniformly coated on a PET base film, cured at 80°C for 20 min, and then cut into 10 cm×5 cm specifications and pasted on a standard steel plate to make samples. According to GB / T2792-2014 "Test method for peel strength of adhesive tapes", the samples and the samples treated in a constant temperature box at 100°C for 24 h were subjected to a 180° peel strength test to determine the peel strength and high temperature resistance of the samples; according to GB / T 4852-2002 "Test method for initial adhesion of pressure-sensitive adhesive tapes (rolling ball method)", the samples were subjected to an initial adhesion test to determine the bonding strength of the samples. The specific test results are shown in Table 1:

[0072] Table 1 - Performance Test

[0073]

[0074] From the test results in Table 1, it can be seen that the sealants prepared in Examples 1 to 3 are at an excellent level in terms of both high temperature resistance and bonding strength; in the sealant prepared in Comparative Example 1, only the composite tackifier is added, and the bonding strength of the sealant is good, and the peel strength decreases significantly after high temperature treatment. Compared with the examples, the high temperature resistance of the sealant is average; in the sealant prepared in Comparative Example 2, no composite tackifier is used as a modifier. Compared with the examples, the bonding strength of the sealant is poor, but a high temperature resistant modifying component is added, and the high temperature treatment of the sealant is poor. The decrease in post-peel strength is small, so it has excellent high temperature resistance; 3,4-dihydroxybenzoic acid and high temperature resistant modified components are added to the sealant prepared in Comparative Example 3. Compared with the embodiment, the high temperature resistance of the sealant is better, but the bonding strength of the sealant is average. It is speculated that this may be because there is no cross-linking with the matrix, and 3,4-dihydroxybenzoic acid migrates in the matrix, resulting in a decrease in the bonding performance of the sealant; No composite tackifier and high temperature resistant modified component are added to the sealant prepared in Comparative Example 4, so the performance of each sample is the worst.

[0075] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A sealant for manufacturing new energy vehicles, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of acrylic acid, 20-30 parts of butyl methacrylate, 10-20 parts of acrylamide, 5-10 parts of glycidyl acrylate, 4-8 parts of composite tackifier, 20-40 parts of deionized water, 0.5-1.5 parts of benzoyl peroxide, 3-6 parts of high temperature resistant modification components, 6-8 parts of fillers, 1-3 parts of dispersants and 1-2 parts of film-forming aids.

2. A sealant for manufacturing new energy vehicles according to claim 1, characterized in that: The preparation method of the composite tackifier comprises the following steps: D1: Under nitrogen protection, 1,3-diamino-2-propanol, 2,3-dichloropropylene and dimethyl sulfoxide solution were stirred and mixed, and stirred at a constant temperature of 70-80°C for 5-10 hours, and then discharged after cooling to room temperature to obtain an intermediate material; D2: Under continuous nitrogen conditions, the intermediate material and 3,4-dihydroxybenzoic acid were added to N-methylpyrrolidone, stirred evenly, and then an esterification catalyst was added. The system temperature was raised to 95-105°C, stirred for 4-8 hours, and the solvent was removed by rotary evaporation to obtain a composite tackifier.

3. A sealant for manufacturing new energy vehicles according to claim 2, characterized in that: In step D2, the esterification catalyst is any one of p-toluenesulfonic acid, aminosulfonic acid or trifluoromethanesulfonic acid.

4. The sealant for manufacturing new energy vehicles according to claim 1, characterized in that: The preparation method of the high temperature resistant modified component comprises the following steps: DD1: under the action of the accelerator, polyphenylene ether and 4-bromobutyric acid are added to the xylene solution, magnetically stirred evenly, the temperature is raised to 75-85°C, stirred for 5-7 hours, and discharged to obtain modified polyphenylene ether; DD2: Add modified polyphenylene ether, trimethylsilyl alcohol and N,N-dimethylformamide into the reaction kettle, stir evenly, add p-toluenesulfonic acid, stir at a constant temperature of 95-105°C for 5-7h, cool and discharge the material to obtain a high temperature resistant modified component.

5. A sealant for manufacturing new energy vehicles according to claim 4, characterized in that: In step DD1, the number average molecular weight of the polyphenylene ether is 500-3000.

6. The sealant for manufacturing new energy vehicles according to claim 4, characterized in that: In step DD1, the promoter is any one of sodium carbonate, potassium carbonate or sodium bicarbonate.

7. The sealant for manufacturing new energy vehicles according to claim 4, characterized in that: In step DD2, the mass ratio of the modified polyphenylene ether to trimethylsilyl alcohol is 1:0.1-0.

3.

8. The sealant for manufacturing new energy vehicles according to claim 1, characterized in that: The filler is any one of calcium carbonate, hydrotalcite or titanium dioxide; the dispersant is any one of sodium tripolyphosphate, sodium hexametaphosphate or sodium pyrophosphate; the film-forming aid is any one of 1,2-propylene glycol, propylene glycol methyl ether acetate or methyl benzyl alcohol.

9. A method for producing a sealant for manufacturing new energy vehicles according to claim 1, characterized in that: The following steps are involved: (i) adding acrylic acid, butyl methacrylate, acrylamide, glycidyl acrylate, composite tackifier and deionized water into a reaction kettle, stirring evenly with magnetic force, passing nitrogen, exhausting air, adding benzoyl peroxide into the reaction kettle, raising the system temperature to 60-70° C., stirring for 1-3 hours, and obtaining a mixture; (ii) Add high temperature resistant modified components, fillers, dispersants and film-forming aids to the mixture, stir evenly at room temperature to obtain a sealant.

Citation Information

Patent Citations

  • A high-temperature resistant UV-curable sealant and its preparation method

    CN114032036B

Cited By

  • Adhesive sealant and application thereof

    CN122465554A